PENGARUH CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN DI BURSA EFEK INDONESIA, JAKARTA - Mulia Saputra (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2010)
Researches on the influence of corporate governance on firm value have been widelyconducted, however results inconsistency occurred. Corporate governance , whichin this case is ownership structure assessed by present of ownership structure. Thisresearch uses 150 manufacturing firms listed on the Jakarta Stock Exchange during2002 - 2005 as samples with 600 observation Hypothesis is tested using regressionanalysis The firm value measured using Tobin’s Q. Results indicate that familyownership, institution ownership and foreign ownership was not significant effecton firm value. but managerial ownership, have a significant and positive effect onfirm value.Keywords: Family Ownership, Institution ownership, managerial ownership, foreignownership and firm value